Confidence vs. Anxiety: Unveiling the Link Between Self-Efficacy and Math Anxiety - Octaviani, Anggun; Sundari, Marta (Asosiasi Asesmen Pendidikan (AAP), 2024)
Background of the study: the aim of this research is to find out whether there is a relationship between self-efficacy and mathematics anxiety and aims to see a picture of students' self-efficacy and mathematics anxiety. The method used in this research uses a quantitative approach. The population and sample in this research were 189 Bina Dharma Jakarta Middle School students. Data were analysed using SPSS version 27 software with correlational techniques. The findings in this research are that there is a significant relationship between self-efficacy (X) and mathematics anxiety (Y), seen from the contribution made by self-efficacy of 17.6% to mathematics anxiety. The relationship between levels of self-efficacy and mathematics anxiety is in the moderate relationship category with a significance value of -0.419 (negative), so it can be stated that an increase in students' self-efficacy causes a decrease in mathematics anxiety.